Silver Chloride Precipitation-limiting Factor for Accurate Silver Determination in Ag-accumulating Mushrooms After Nitric Acid Digestion - Synková, Iva; Borovička, Jan (Biological trace element research, 2025)
Wild-growing mushrooms (macromycetes, macrofungi) are capable of accumulating high amounts of trace elements, including noble metals. In a series of analytical experiments, this study focused on the problem of correct determination of Ag mass fractions in the biomass of Ag-accumulating mushrooms, Ag-hyperaccumulators in particular. A unique experimental setup enabled to compare Ag determination in selected mushroom samples first by the non-destructive neutron activation analysis (INAA) utilizing 110Ag isotope, second by the high-resolution inductively coupled plasma mass spectrometry (HR-ICP-MS) after HNO3 hotplate and microwave digestions. Furthermore, Ag-spiking experiments were conducted with three mushroom species containing 860, 6200, and 21,000 mg Cl kg-1 in dry mass and Ag was determined by HR-ICP-MS after HNO3 hotplate digestion of the samples. Finally, ten replicates of Ag-hyperaccumulating Amanita strobiliformis were analyzed by two variants of INAA utilizing 108Ag in the first step and 110 mAg isotope in the second step. In addition, four additional digestion procedures followed by HR-ICP-MS and inductively coupled plasma optical emission spectroscopy (ICP-OES) measurements of Ag were performed on this A. strobiliformis sample. Analytical quality was controlled by using NIST Standard Reference Materials 1566b (Oyster Tissue) and 2781 (Domestic Sludge). The results of all experiments revealed that correct determination of Ag in mushrooms is not always possible using standard digestion procedures because of precipitation of insoluble AgCl which was documented by scanning electron microscopy and confirmed by the X-ray diffraction analysis.
Keywords: stříbro; Agaricales; HR-ICP-MS; ICP-OES; INAA; Standard reference materials; Silver; sloučeniny stříbra; Microwave digestion; Silver Compounds; hmotnostní spektrometrie; Hyperaccumulation; Chemical Precipitation; Mass Spectrometry; kyselina dusičná; Nitric Acid; chemická precipitace; Fungi